Peran Wahid Hasyim dalam Pendidikan Nadatul Ulama di Indonesia Pada Tahun 1940-1949 - Putri Rizki Mpayang; Aulia Novemy; Dhita Surbakti (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2020)
The study in this article examined Wahid Hasyim role in Islamic education, specifically in its relation to the renewal of Islamic education in the Tebuireng Islamic Boarding School. The method used is a historical method which consists of four steps, namely heuristics, source criticism, interpretation and historiography. Based on the study results, the efforts to renew Islamic education in the Islamic boarding school Tebuireng were initiated by Wahid Hasyim. The pan Islamism movement in the Middle East that spread in the Mecca area had a major influence on the formation of Wahid Hasyim’s Islamic renewal ideas. When he studied in Mecca in 1932, his learning and interaction with people of different nationalities were internalized and shaped his views so that he could initiate ideas for Islamic renewal. When he returned to Tebuireng, Wahid Hasyim proposed to Hasyim Asy’ari to make an advance on the teaching methods and materials at the Tebuireng boarding school.